2018
DOI: 10.1007/s12192-017-0830-9
|View full text |Cite
|
Sign up to set email alerts
|

Systematic identification and characterization of stress-inducible heat shock proteins (HSPs) in the salmon louse (Lepeophtheirus salmonis)

Abstract: Salmon lice (Lepeophtheirus salmonis) are parasitic copepods, living mainly on Atlantic salmon and leading to large economical losses in aquaculture every year. Due to the emergence of resistances to several drugs, alternative treatments are developed, including treatment with hydrogen peroxide, freshwater or thermal treatment. The present study gives a first overview of the thermotolerance and stress response of salmon lice. Sea lice nauplii acclimated to 10 °C can survive heat shocks up to 30 °C and are capa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…Initially, the genes coding for Hsp70 were identified as chromosome puffs in Drosophila after heat shock treatment in 1962, and subsequently accumulating evidence on Hsp functions suggests that Hsp could be induced by not only heat stresses but also many other abiotic and/or biotic challenges, such as osmotic pressure, heavy metal, ultraviolet radiation, oxidative stress, and bacteria infection ( Sørensen et al, 2003 ). Although the relationship between induced Hsp expression and stress resistance has been widely studied and confirmed in an array of species, the stress response processes associated with Hsp are still complicated and not well systematically resolved, mainly due to the following aspects: (1) not all Hsp members can be induced by stresses, and some constitutively expressed Hsp also play important roles for survival under non-stressful conditions ( Borchel et al, 2017 ), (2) different Hsp members with distinct molecular structures showed diverse functions in response to the same types of stresses ( Fujikawa et al, 2010 ), (3) the induction of Hsp expression by different stresses may vary with stress types and/or intensities ( Cellura et al, 2006 ; Dong et al, 2008 ), (4) the roles of Hsp in adapting to the same stressful environments are species-specific ( Serafini et al, 2011 ), (5) mechanisms of Hsp expression are multi-layered regulated, including transcriptional control by binding of heat shock factor (Hsf) to heat shock elements (HSEs) at the promoter region of heat shock genes, as well as at the translation and even DNA methylation levels ( Serafini et al, 2011 ; Pu and Zhan, 2017 ), and (6) individuals living in distinct environments often use different strategies for adaptation, such as preadaptation and/or up-regulation of Hsp expression in response to stresses ( Gleason and Burton, 2015 ). As a result, systematic identification of a complete set of Hsp and Hsf genes across the whole genome and comprehensive investigation of their response patterns to environmental stresses are necessary for clarifying the adaptive roles of Hsp in ecological and evolutionary studies.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, the genes coding for Hsp70 were identified as chromosome puffs in Drosophila after heat shock treatment in 1962, and subsequently accumulating evidence on Hsp functions suggests that Hsp could be induced by not only heat stresses but also many other abiotic and/or biotic challenges, such as osmotic pressure, heavy metal, ultraviolet radiation, oxidative stress, and bacteria infection ( Sørensen et al, 2003 ). Although the relationship between induced Hsp expression and stress resistance has been widely studied and confirmed in an array of species, the stress response processes associated with Hsp are still complicated and not well systematically resolved, mainly due to the following aspects: (1) not all Hsp members can be induced by stresses, and some constitutively expressed Hsp also play important roles for survival under non-stressful conditions ( Borchel et al, 2017 ), (2) different Hsp members with distinct molecular structures showed diverse functions in response to the same types of stresses ( Fujikawa et al, 2010 ), (3) the induction of Hsp expression by different stresses may vary with stress types and/or intensities ( Cellura et al, 2006 ; Dong et al, 2008 ), (4) the roles of Hsp in adapting to the same stressful environments are species-specific ( Serafini et al, 2011 ), (5) mechanisms of Hsp expression are multi-layered regulated, including transcriptional control by binding of heat shock factor (Hsf) to heat shock elements (HSEs) at the promoter region of heat shock genes, as well as at the translation and even DNA methylation levels ( Serafini et al, 2011 ; Pu and Zhan, 2017 ), and (6) individuals living in distinct environments often use different strategies for adaptation, such as preadaptation and/or up-regulation of Hsp expression in response to stresses ( Gleason and Burton, 2015 ). As a result, systematic identification of a complete set of Hsp and Hsf genes across the whole genome and comprehensive investigation of their response patterns to environmental stresses are necessary for clarifying the adaptive roles of Hsp in ecological and evolutionary studies.…”
Section: Introductionmentioning
confidence: 99%
“…Calanus sinicus (Zhou et al, 2016) No (Lauritano et al, 2015) Yes Lepeophtheirus salmonis (Tribble et al, 2007) No (Borchel et al, 2018;Park et al, 2017) Yes Paracyclopina nana (Jeong et al, 2015) Yes Pseudodiaptomus poplesia (Zhuang et al, 2017) Yes Tigriopus japonicus (Park et al, 2017) No (Jeong et al, 2015;Lee et al, 2017) Yes…”
Section: Accepted M M a N U mentioning
confidence: 99%
“…Altered regulation of these pathways is likely energetically expensive, particularly for non-feeding larval stages (Sutherland et al 2012). Upregulation of HSPs, which can also be important for 'hardening' an individual to future instances of a stressful condition, has been found in response to lower-salinity water by both Sutherland et al (2012) and Borchel et al (2018), although in both cases, only a few HSPs were upregulated and to a relatively low degree compared to a simultaneously conducted thermal challenge. Sutherland et al (2012) and Borchel et al (2018) used different subspecies of Lepeophtheirus salmonis, namely L. salmonis oncorhynchi (Pacific) and L. salmonis salmonis (Atlantic), respectively, showing that, despite significant environmental and evolutionary pressures linked to phenotypic differences between these subspecies, salinity stress responses were conserved.…”
Section: Mechanisms Of Freshwater Tolerancementioning
confidence: 99%
“…Upregulation of HSPs, which can also be important for 'hardening' an individual to future instances of a stressful condition, has been found in response to lower-salinity water by both Sutherland et al (2012) and Borchel et al (2018), although in both cases, only a few HSPs were upregulated and to a relatively low degree compared to a simultaneously conducted thermal challenge. Sutherland et al (2012) and Borchel et al (2018) used different subspecies of Lepeophtheirus salmonis, namely L. salmonis oncorhynchi (Pacific) and L. salmonis salmonis (Atlantic), respectively, showing that, despite significant environmental and evolutionary pressures linked to phenotypic differences between these subspecies, salinity stress responses were conserved. Going one step further, Borchel et al (2018) noted that 2 of the HSPs expressed by L. salmonis salmonis copepodids in response to salinity stress were also induced following exposure to the anti-louse treatment hydrogen peroxide.…”
Section: Mechanisms Of Freshwater Tolerancementioning
confidence: 99%
See 1 more Smart Citation